The Impacts of Urban Morphology on Housing Indoor Thermal Condition in Hoi An City, Vietnam - Huong Thien LUU; Juan Carlos Rojas-Arias; Dominique Laffly (Alanya Hamdullah Emin Paşa Üniversitesi, 2021)
Assessing the impact of urban morphology on the indoor thermal condition of housing in a tourism city in central Vietnam — Hoi An City is the main objective of this study. The research process is carried out by a variety of methods including in situ surveys, measuring with temperature sensors, data analysis and map analysis. Four houses, located in two areas with different urban forms, were selected for measurement within one month to investigate the differences in housing indoor temperature. The impact of urban morphology on housing was thereafter determined. Temperature sensors were permanently installed in 4 houses; based on these empirical measurements and data collected, the paper addresses solutions to improve urban morphology and indoor thermal condition.